(untitled) (Journal of Human Sciences, 2023)
The title of the research is facing university professors in southern Libya in applying the e-learning program in light of the conditions that the Libyan state is going through and the Corona pandemic. Where the search aims to The research aims to identify the difficulties facing university professors in applying the e-learning program in light of the conditions the Libyan state is going through and the Corona pandemic. questionnaire consisting of 30 items. To achieve the purposes of scientific research, the analytical descriptive approach was adopted, and the sample consisted of (60) respondents among males and females from different colleges who were chosen randomly. The statistical methods used the frequency table and percentages. The search results were as follows: 1/ The results showed that 90% applied the e-learning program, as well as the results showed that there were several difficulties faced by the university professor in southern Libya when applying the e-learning program, as it is not in line with the current conditions of the Libyan state. 2/ The results showed, with a percentage of 90%, that the current conditions of the country in terms of power outages and the interruption of Internet services are not compatible with the idea of implementing e-learning. 3/ Studies showed, with a percentage of 33.3 of the respondents, that the administration was supportive hand in hand with the university professor and the student, and with a percentage of 66.7 of the respondents, it showed that the administration was not supportive. 4/ The results showed, by 93% of the respondents, that the administration did not provide all means of assistance, nor did it consider their circumstances. 5/ The results of the research confirmed by 83% of the respondents that the conditions of the Libyan south are not compatible with the idea of implementing the e-learning program. 6/ The results of the research indicated that 87% of the respondents demanded the adoption of e-learning in addition to traditional education in the future